Cross Section Measurements of (n,p) Reactions on Ge Isotopes - Gkatis, G.; Vlastou, Rosa; Kalamara, A.; Chasapoglou, S.; Kokkoris, M.; Axiotis, M.; Lagoyannis, A.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2020)
The 72,73Ge(n,p)72,73Ga reaction cross sections were measured at the 5.5MV HV Tandem accelerator of NCSR “Demokritos”, at neutron energies 17.7 and 19.3 MeV by using the activation method. The contamination from the (n,d) and (n,np) reactions on 73Ge and 74 Ge, leading to the 72Ge and 73Ge residual nuclei, respectively, has been taken into account, implementing the corresponding cross sections from TENDL-2017. A systematic investigation of the isotopic effect on all Ge isotopes is also presented, from threshold up to 20MeV, using the present data along with existing data in literature